2018
DOI: 10.1093/ndt/gfy247
|View full text |Cite|
|
Sign up to set email alerts
|

The association of interdialytic blood pressure variability with cardiovascular events and all-cause mortality in haemodialysis patients

Abstract: Increased BPV during the interdialytic interval is associated with higher risk of death and cardiovascular events, whereas ambulatory BP levels are not. This association was not independent after adjustment for PWV, other risk factors and prevalent cardiovascular disease. Short-term BPV could be a mediator promoting the adverse cardiovascular profile of haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…We observed that all indices examined were significantly higher during the 2nd in comparison to the 1st 24-h period of the interdialytic interval [3]. In a subsequent prospective cohort study of 227 patients and average 2.5 years of follow-up, we observed that all of SD, wSD, CV, and ARV indexes measured over the 48-h period were associated to the future risk of cardiovascular events and mortality [16], thus adding BPV to the complex set of factors involved in the adverse cardiovascular profile of hemodialysis individuals.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We observed that all indices examined were significantly higher during the 2nd in comparison to the 1st 24-h period of the interdialytic interval [3]. In a subsequent prospective cohort study of 227 patients and average 2.5 years of follow-up, we observed that all of SD, wSD, CV, and ARV indexes measured over the 48-h period were associated to the future risk of cardiovascular events and mortality [16], thus adding BPV to the complex set of factors involved in the adverse cardiovascular profile of hemodialysis individuals.…”
Section: Discussionmentioning
confidence: 59%
“…A recent study that examined short-term BPV by 24-h ABPM in a large sample of hypertensive patients with different stages of CKD has shown that BPV is increasing as CKD stage advances [15]. In hemodialysis, we recently showed that BPV is increased from Day 1 to Day 2 of the interdialytic interval [3], and that all indexes of BPV are associated with increased risk of cardiovascular events and death [16]. We have also recently showed that nebivolol and irbesartan are able to reduce ambulatory BP in patients with intradialytic hypertension [17].…”
Section: Introductionmentioning
confidence: 99%
“…One study presented overlapping data using the same datasets and was excluded [19]. Ultimately, the review included 15 eligible studies [18, 20-25, 35-42]. Results from 2 studies did not provide sufficient data for the pooled analysis [22, 42].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found an association between the mean BP and outcomes in patients on HD [15-17]. Over the last decade, more studies have explored the impact of BPV on the prognosis of HD patients, with inconsistent results [18-25]. Therefore, we conducted a systematic review and meta-analysis to assess the prognostic significance of BPV on cardiovascular and all-cause mortality and cardiovascular events in ESRD patients on dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive interdialytic fluid gains contribute to the development of LVH 25 and associate with worse outcomes, 26 although recent data suggest that this association is also affected by an interaction with nutritional status 27 . The degree to which blood pressure varies in the interdialytic period also has been linked to worse outcomes, 28 and the longer interdialytic gap is associated with increased rates of sudden cardiac death in HD patients. 24 Earlier studies reported that mortality events occurred in a bimodal distribution, with mortality more common at the end of and immediately after the long interdialytic gap, suggesting that both accumulation and fluctuations of fluid/uremic toxins with dialysis lead to higher mortality.…”
Section: Dialysis-induced Myocardial Hypoperfusion Has Been Directly mentioning
confidence: 99%